Thymic atrophy in cattle poisoned with Solanum glaucophyllum - Fontana, Paula Andrea (2009)
Solanum glaucophyllum (Sg) [= S. malacoxylon] is a calcinogenic plant inducing "Enzootic Calcinosis" in cattle. The 1,25-dihydroxyvitamin D3, its main toxic principle, regulates bone and calcium metabolism and also exerts immunomodulatory effects. Thymocyte precursors from bone marrow-derived progenitor cells differentiate into mature T-cells. Differentiation of most T lymphocytes is characterized not only by the variable expression of CD4/CD8 receptor molecules and increased surface density of the T cell antigen receptor, but also by changes in the glycosylation pattern of cell surface glycolipids or glycoproteins. Thymocytes exert a feedback influence on thymic non-lymphoid cells. Sg-induced modifications on cattle thymus T-lymphocytes and on non-lymphoid cells were analysed. Heifers were divided into 5 groups (control, intoxicated with Sg during 15, 30 or 60 days, and probably recovered group). Histochemical, immunohistochemical, lectinhistochemical and morphometric techniques were used to characterize different cell populations of the experimental heifers. Sg-poisoned heifers showed a progressive cortical atrophy that was characterized using the peanut agglutinin (PNA) lectin that recognizes immature thymocytes. These animals also increased the amount of non-lymphoid cells per unit area detected with the Picrosirius technique, WGA and DBA lectins, and pancytokeratin and S-100 antibodies. The thymus atrophy found in intoxicated animals resembled that of the physiological aging process. A reversal effect on these changes was observed after suppression of the intoxication. These findings suggest that Sg-intoxication induces either directly, through the 1,25-dihydroxyvitamin D3 itself, or indirectly through the hypercalcemia, the observed alteration of the thymus.